2023
DOI: 10.1186/s13012-023-01286-z
|View full text |Cite|
|
Sign up to set email alerts
|

Ten years of implementation outcomes research: a scoping review

Abstract: Background Proctor and colleagues’ 2011 paper proposed a taxonomy of eight implementation outcomes and challenged the field to address a research agenda focused on conceptualization, measurement, and theory building. Ten years later, this paper maps the field’s progress in implementation outcomes research. This scoping review describes how each implementation outcome has been studied, research designs and methods used, and the contexts and settings represented in the current literature. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 70 publications
3
29
0
Order By: Relevance
“…Implementation and contextual factors (barriers and facilitators) will be further assessed using the Consolidated Framework for Implementation Research [30] and Proctor's framework [31,32]. A 13 secondary grounded theory analysis will be undertaken to generate theory to explore and explain the phenomenon of adolescent pregnancy in Sierra Leone [33].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation and contextual factors (barriers and facilitators) will be further assessed using the Consolidated Framework for Implementation Research [30] and Proctor's framework [31,32]. A 13 secondary grounded theory analysis will be undertaken to generate theory to explore and explain the phenomenon of adolescent pregnancy in Sierra Leone [33].…”
Section: Discussionmentioning
confidence: 99%
“…Proctor’s evaluative framework consists of healthcare service (Efficiency, safety, effectiveness, equity, patient centeredness, timeliness) and implementation (acceptability, adoption, appropriateness, cost, feasibility, fidelity, penetration, sustainability) outcomes. These are well-used constructs in the implementation science literature since 2011, in over 400 papers as a standard measure of implementation outcomes [ 19 ]. These measures, and their definitions in the genomic MDT context, were further characterized by GMIR domain mapping to understand the genomic MDT outcomes (Supp table S 2 ) by two authors prior to extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Reviews of the current mental health system in Australia, and the state of Victoria in particular, have highlighted the need to consider how mental health services are designed, implemented and delivered. 10,19,20 The 2023 Victorian Royal Commission into the Mental Health System reported that the system required significant reform. 19,20 A major recommendation of the commission was to embed codesign into mental health interventions and treatment programmes.…”
Section: Background For This Studymentioning
confidence: 99%
“…10,19,20 The 2023 Victorian Royal Commission into the Mental Health System reported that the system required significant reform. 19,20 A major recommendation of the commission was to embed codesign into mental health interventions and treatment programmes. The intervention referenced in this paper is an intense, psychosocial out-reach model of care, designed for young people aged 12-26 with persistent suicidal ideation or postsuicide attempt.…”
Section: Background For This Studymentioning
confidence: 99%
See 1 more Smart Citation